The moonstone - Collins, Wilkie, 1824-1889 (Knopf : Distributed by Random House, 1992)
The Moonstone was first published in 1868 and concerns a huge yellow diamond that was once stolen from an Indian shrine. Rachel Verrinder receives the stone as a gift and does not realize that it has been passed to her in a sinister form of revenge by John Herncastle who, it transpires, acquired the moonstone by means of murder and theft. The jewel also brings bad luck. The stone disappears on the very night it is given to Rachel and the tale concerns the unveiling of the culprit. A maid who is under suspicion commits suicide and Rachel herself seems reticent when it comes to aiding the investigation. Mysterious Indians appear frequently and there is an air of confusion and the unknown until the mystery is eventually solved.